Measuring the production of marine phytoplankton - Strickland, J. D. H. (Ottawa, Canada The Fisheries Research Board of Canada, 1960)
Contents : No. 122 : Measuring the production of marine phytoplankton No. 125 : A manual of sea water analysis
Keywords: Sea water; Phytoplankton; Marine phytoplankton; PhotosynthesisPhotosynthesis